Multiphoton, multimode state classification for nonlinear optical circuits - Denis A. Kopylov; Christian Offen; Laura Ares; Boris Wembe; Sina Ober-Blöbaum; Torsten Meier; Polina R. Sharapova; Jan Sperling (Physical Review Research, 2025)
We introduce a new classification of multimode states with a fixed number of photons. This classification is based on the factorizability of homogeneous multivariate polynomials and is invariant under unitary transformations. The classes physically correspond to field excitations in terms of single and multiple photons, each of which is in an arbitrary irreducible superposition of quantized modes. We further show how the transitions between classes are rendered possible by photon addition, photon subtraction, and photon-projection nonlinearities. We explicitly put forward a design for a multilayer interferometer in which the states for different classes can be generated with state-of-the-art experimental techniques. Limitations of the proposed designs are analyzed using the introduced classification, providing a benchmark for the robustness of certain states and classes.